Search Theory and Commuting Behavior - Jan Rouwendal (Tinbergen Institute, 2004)
In this paper I argue that search theory is a useful addition to the way economists and geographers have approached the study of commuting behavior. This is illustrated by showing that introduction of a spatial element into the standard model of job search leads to the prediction of critical isochrones. Moreover, in the context of an urban economy with decentralized employment the spatial search model predicts excess commuting. Search theory also suggests that regression towards the mean may play a confusing role in data describing the development of commutes over time, such as has been used in recent empirical work. Finally, the paper develops a simple spatial equilibrium search model in which employers set their wages optimally and searchers determine their reservation wages optimally in mutually consistent ways. The spatial element is crucial for the existence of such an equilibrium in which reservation wages of all searchers and wages set by all employers are identical.
Keywords: J64; R41; R23; 330; commuting; search theory; local labor markets; Suchtheorie; Suchtheorie; Pendelverkehr